PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP MOTIVASI DAN HASIL BELAJAR IPAS SISWA KELAS VI SDN 25/II MUARA BUNGO - Meggi; Megawati; Apdoludin (STKIP Subang, 2025)
This study is entitled The Influence of the Flipped Classroom Learning Model on the Motivation and Learning Outcomes of Class VI Students of SDN 25/II Muara Bungo, with the aim of finding out whether there is an influence on the learning motivation and learning outcomes of class VI students of SDN 25/II Muara Bungo before being given treatment (treatment) and after being given treatment (treadmen) at the time of the posttest and to find out whether the flipped classroom model can improve the motivation and learning outcomes of class VI students at SDN 25/II Muara Bungo. Many factors influence motivation and learning outcomes, one of which is the learning model applied by teachers in the classroom.The method used in this research is the pre-experimental type experimental method and the research design is a one group pretest posttest design, the object of the research is grade VI students with a total of 15 students.Motivation and learning motivation data were obtained from the results of the pretest and posttest in the form of questionnaires and test questions in the form of multiple choice questions. The results of this study showed a difference in learning motivation results of 62.86 for the pretest results, and 73.33 for the posttest results. And the difference in learning outcomes was 68.47 for the pretest results, and 87.00 for the posttest results. This is evidenced by the paired sample test value for learning motivation showing that the significance value of 0.00 is smaller than the specified alpha value of 0.05. Likewise, the value of the learning outcomes shows that 0.00 is smaller than the specified alpha value of 0.05, so that h01 is rejected and ha1 is accepted. And also H02 is rejected and ha2 is accepted.The conclusion is that there is an influence on the results of learning motivation and learning outcomes of grade VI students in science using the flipped classroom model. From the results of the study, it is recommended that the flipped classroom model learning can increase student motivation and learning outcomes, and should be used as an alternative in science learning activities, especially in the human movement system material.